Comparison of cardiovascular disease risk in two main forms of periodontitis - Rahul Chopra; Sudhir R Patil; Shivani Mathur (Wolters Kluwer Medknow Publications, 2012)
Background: C-reactive protein (CRP) is an acute phase reactant and has been proved to be a significant predictor of future cardiovascular events. Recent studies have demonstrated a correlation between periodontitis and elevated CRP levels. However, comparison between the levels of CRP in two main forms of periodontitis is ambiguous. This study aims at determining and comparing the relative levels of serum CRP in aggressive and chronic periodontitis patients. Materials and Methods: A total of 240 systemically healthy subjects were divided into three groups of 80 based on having generalized aggressive periodontitis, chronic generalized periodontitis and non-periodontitis (NP; controls). Venous blood samples were collected for quantitative CRP analysis using turbidimetric immunoassay. Results: Mean CRP levels were significantly greater in both generalized aggressive periodontitis (7.49±2.31 mg/l) and chronic generalized periodontitis (4.88±1.80 mg/l) groups as compared to NP (0.68±0.23 mg/l) controls. Moreover, CRP levels were significantly higher in aggressive periodontitis as compared to chronic periodontitis patients. Also, CRP levels positively correlated with the amount of periodontal destruction as measured by probing depth and clinical attachment loss for both chronic generalized periodontitis and generalized aggressive periodontitis. Conclusion: Findings of the present study indicated that periodontitis should be of particular concern in younger individuals, where elevated levels of CRP may contribute to early or more rapid cardiovascular disease in susceptible patients. Thus, further research should be carried out at a community level to ascertain these findings.